Mortality in infants with bronchopulmonary dysplasia: Data from cardiac catheterization. Issue 6 (2nd April 2019) - Steurer, Martina A.; Nawaytou, Hythem; Guslits, Elyssa; Colglazier, Elizabeth; Teitel, David; Fineman, Jeffrey R.; Keller, Roberta L.
Abstract: Rationale: Pulmonary hypertension (PH) is relatively common in infants with severe bronchopulmonary dysplasia (BPD), however, hemodynamic data and factors associated with mortality in this patient group are sparsely described in the literature. Objectives: To characterize the hemodynamics of former preterm infants with BPD and PH, as measured at cardiac catheterization, and to identify respiratory and cardiovascular predictors of mortality. Methods: Single‐center, retrospective cohort study, including, 30 patients born at less than 32‐week gestational age (GA), who had an oxygen requirement at 36 weeks postmenstrual age and underwent cardiac catheterization between July 2014 and December 2017. Results: Median GA at birth was 25 5/7 weeks (interquartile range [IQR], 24 4/7‐26 6/7 weeks). Median birth weight was 620 g (IQR, 530‐700 g). With a median of 23 months of follow up (IQR, 11‐39 months), mortality as of July 2018 was 27% (8 of 30). The alveolar‐arterial oxygen gradient as a measure of lung disease did not correlate with mortality (log‐rank test P = 0.28). However, indexed pulmonary vascular resistance (PVR) of greater than 3 Woods units × m 2 showed a trend toward increased mortality (log‐rank test P = 0.12). Pulmonary vein stenosis was the only predictor significantly associated with mortality (log‐rank test P = 0.005). Conclusions: In this cohort, the severity of lung disease as assessed by impaired oxygenation at cardiac catheterization did not correlate with mortality. The only factor significantly associated with mortality was the presence of pulmonary vein stenosis on cardiac catheterization, although PVR may also be an important factor.